Volunteer motivation: a atudy on AÇEV’s functional adult literacy program volunteers - Balta, Berna. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This study aims to investigate the motivational factors affecting the people to participate voluntary activities. Also, the relationship between demographic characteristics and volunteers’ motivational factors, the relationship between demographic characteristics and volunteers’ intention to continue voluntary work, and the relationship between the volunteer motivation and the volunteers’ intention to continue voluntary work are examined in this study. The sample of the study consists of 71 Functional Adult Literacy Program volunteers who gave literacy courses in the 2007-2008 academic year in Izmir, Bursa, Adana, and Diyarbakır. The results show that the majority of volunteers are between 41-50 years old, graduated from university, married, housewives and unemployed. Volunteers are mostly motivated from altruistic reasons to volunteer, and personal improvement reasons and affiliative reasons are other motivational factors affecting FALP volunteers. The analysis indicates that the participants’ motivations related to personal improvement change through their educational level. However, there is no relationship between other demographic variables and volunteers’ motivation; between demographic variables and volunteers’ intention to continue voluntary work; and also between volunteers’ motivational factors and their intention to continue voluntary work.
Keywords: Volunteer workers in social service.; Volunteers.; Motivation (Psychology)